Nitrogen and phosphorus significantly alter growth, nitrogen fixation, anatoxin-a content, and the transcriptome of the bloom-forming cyanobacterium, Dolichospermum - Kramer, Benjamin J.; Jankowiak, Jennifer G.; Nanjappa, Deepak; Harke, Matthew J.; Gobler, Christopher J. (Frontiers in Microbiology, 2022)
While freshwater cyanobacteria are traditionally thought to be limited by the availability of phosphorus (P), fixed nitrogen (N) supply can promote the growth and/or toxin production of some genera. This study characterizes how growth on N2 (control), nitrate (NO3–), ammonium (NH4+), and urea as well as P limitation altered the growth, toxin production, N2 fixation, and gene expression of an anatoxin-a (ATX-A) – producing strain of Dolichospermum sp. 54. The transcriptomes of fixed N and P-limited cultures differed significantly from those of fixed N-deplete, P-replete (control) cultures, while the transcriptomes of P-replete cultures amended with either NH4+ or NO3– were not significantly different relative to those of the control. Growth rates of Dolichospermum (sp. 54) were significantly higher when grown on fixed N relative to without fixed N; growth on NH4+ was also significantly greater than growth on NO3–. NH4+ and urea significantly lowered N2 fixation and nifD gene transcript abundance relative to the control while cultures amended with NO3– exhibited N2 fixation and nifD gene transcript abundance that was not different from the control. Cultures grown on NH4+ exhibited the lowest ATX-A content per cell and lower transcript abundance of genes associated ATX-A synthesis (ana), while the abundance of transcripts of several ana genes were highest under fixed N and P - limited conditions. The significant negative correlation between growth rate and cellular anatoxin quota as well as the significantly higher number of transcripts of ana genes in cultures deprived of fixed N and P relative to P-replete cultures amended with NH4+ suggests ATX-A was being actively synthesized under P limitation. Collectively, these findings indicate that management strategies that do not regulate fixed N loading will leave eutrophic water bodies vulnerable to more intense and toxic (due to increased biomass) blooms of Dolichospermum.